(untitled) (Scientific journal of the Fergana State University, 2025)
The basic level of organization of elementary soil particles determines the fundamental properties and biogeochemical processes, energy and mass exchange, absorption and transformation of substances and functioning of the soil in the biosphere. Studies of these properties and processes are possible only taking into account the dispersion of the solid phase of the soil, i.e. its granulometric composition. The paper presents the main classification concepts of soil granulometry, research methods and analysis of results.